2013
DOI: 10.1111/apha.12163
|View full text |Cite
|
Sign up to set email alerts
|

Relative contribution of foetal and post‐natal nutritional periods on feeding regulation in adult rats

Abstract: Altogether, these results indicate that peri-natal nutrition has different lasting effects on feeding pattern and hypothalamic appetite regulation, depending on the time window insult.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 74 publications
(136 reference statements)
1
8
0
Order By: Relevance
“…Among the environmental stressors that may have an effect, it is suggested in both animal and human studies that perinatal nutrition could program the appetite (see [5,6] for reviews). In rodents, experiments based on restricting maternal nutrition and/or manipulating litter size have demonstrated that both pre- and post-natal nutrition may alter food intake [7,8,9] and/or food preference [10] in offspring, with subsequent repercussions in adulthood. In humans, although controversial results have been observed concerning the influence of prenatal nutrition on later eating behavior (see [11] for review), some observational evidence suggests that early nutrition/growth affects appetite regulation [12,13,14] and food preference programming, as demonstrated after repeated exposure to new flavors [15].…”
Section: Introductionmentioning
confidence: 99%
“…Among the environmental stressors that may have an effect, it is suggested in both animal and human studies that perinatal nutrition could program the appetite (see [5,6] for reviews). In rodents, experiments based on restricting maternal nutrition and/or manipulating litter size have demonstrated that both pre- and post-natal nutrition may alter food intake [7,8,9] and/or food preference [10] in offspring, with subsequent repercussions in adulthood. In humans, although controversial results have been observed concerning the influence of prenatal nutrition on later eating behavior (see [11] for review), some observational evidence suggests that early nutrition/growth affects appetite regulation [12,13,14] and food preference programming, as demonstrated after repeated exposure to new flavors [15].…”
Section: Introductionmentioning
confidence: 99%
“…At adulthood, FI seems grossly normal but a delay in satiation (7) and an increase of the first-meal size following 48-h fasting are still observed suggesting a persistent alteration of short-term regulation of FI. Such an alteration could predispose to obesity particularly when the animals are challenged with a high-calories diet (8). Interestingly, a very recent study showed that LP rats are hyperphagic at older age (1-year old) than younger adult ages usually studied, reinforcing the importance of long lasting impact of programming hyperphagia by perinatal nutrition (35).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in our laboratory demonstrated that low-protein (LP) rats eat more of a regular chow diet from weaning to 2-month old (6, 7). At adulthood despite a higher speed of ingestion (6, 8), a delay in appearance of satiety (satiation) is still observed with more food consumed during the first meal (7). LP rats have also a greater appetite for high-energy diet at adulthood (8) and a preference for high-fat food in the offspring of undernourished dams has also been reported (9), which could contribute to an increase of the body weight during adulthood and later on to obesity.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated the importance of proteins during gestation and/or lactation on pancreas development using a maternal protein restriction model. A general characteristic observed in offspring is the reduction of birth weight without affecting the placenta weight [67,68,77,78,79,80]. When the low protein diet (LP; 8%) is administrated during gestation in the rat, there is a decrease in islet size and beta-cell proliferation in fetuses at 21 days of gestation, as well as a sharp reduction in the vascularization of the islet [67].…”
Section: Influence Of Dietary Intakes During Gestation and Or Lactmentioning
confidence: 99%